Schistosomiasis — assessing progress toward the 2020 and 2025 global goals - Deol,AK; Fleming,FM; Calvo-Urbano,B; Walker,M; Bucumi,V; Gnandou,I; Tukahebwa,EM; Jemu,S; Mwingira,UJ; Alkohlani,A; Traore,M; Ruberanziza,E; et al. (New England Journal of Medicine, 2019)
BackgroundWith the vision of “a world free of schistosomiasis,” the World Health Organization (WHO) set ambitious goals of control of this debilitating disease and its elimination as a public health problem by 2020 and 2025, respectively. As these milestones become imminent, and if programs are to succeed, it is important to evaluate the WHO programmatic guidelines empirically.MethodsWe collated and analyzed multiyear cross-sectional data from nine national schistosomiasis control programs (in eight countries in sub-Saharan Africa and in Yemen). Data were analyzed according to schistosome species (Schistosoma mansoni or S. haematobium), number of treatment rounds, overall prevalence, and prevalence of heavy-intensity infection. Disease control was defined as a prevalence of heavy-intensity infection of less than 5% aggregated across sentinel sites, and the elimination target was defined as a prevalence of heavy-intensity infection of less than 1% in all sentinel sites. Heavy-intensity infection was defined as at least 400 eggs per gram of feces for S. mansoni infection or as more than 50 eggs per 10 ml of urine for S. haematobium infection.ResultsAll but one country program (Niger) reached the disease-control target by two treatment rounds or less, which is earlier than projected by current WHO guidelines (5 to 10 years). Programs in areas with low endemicity levels at baseline were more likely to reach both the control and elimination targets than were programs in areas with moderate and high endemicity levels at baseline, although the elimination target was reached only for S. mansoni infection (in Burkina Faso, Burundi, and Rwanda within three treatment rounds). Intracountry variation was evident in the relationships between overall prevalence and heavy-intensity infection (stratified according to treatment rounds), a finding that highlights the challenges of using one metric to define control or elimination across all epidemiologic settings.Conclusio